Rehabilitation effectiveness after radical surgical treatment of endometrial cancer - D. V. Blinov; A. G. Solopova; E. E. Achkasov; L. N. Sandzhieva; D. I. Korabelnikov; G. K. Bykovshchenko; D. A. Petrenko (IRBIS LLC, 2023)
Aim: to assess an effectiveness of medical rehabilitation after radical surgical treatment of endometrial cancer (EC).  Materials and Methods. Post-surgery EC patients were stratified into two groups: the main group included 29 women who underwent the proposed program of complex "active" medical rehabilitation, the comparison group - 32 patients treated in accordance with the approved clinical guidelines. Body mass index (BMI), waist and hip measurements, atherogenic index, serum glucose, leptin, tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) levels were analyzed at week 1, as well as 3, 6 and 12 months later.  Results. Significant inter-group differences were observed 6 and 12 months later during the follow-up. Starting from 6 months after EC surgical treatment, in the main group BMI decreased reaching 31.14, whereas in the comparison group, it increased up to 35.07 (p < 0.05). Differences in waist and hip measurements became significant by month 6 and 12, respectively, after the onset. The glucose level in the main and comparison group 6 months later was 6.16 ± 0.24 mmol/l and 6.16 ± 0.33 mmol/l, respectively; in the main group it decreased to the norm at month 12 comprising 5.09 ± 0.30 mmol/l, whereas in the comparison group it was higher than normal range reaching up to 5.87 ± 0.27 mmol/l (p < 0. 05). The decrease in the atherogenic index in the main vs. comparison group, which plateaued, became significant at month 6 and 12, respectively. A decrease in serum leptin, TNF-α and IL-6 level was found in the main group, but not in the comparison group.  Conclusion. For the first time, a phenomenon of dynamically decreased level of serum pro-inflammatory markers was established during the complex "active" medical rehabilitation of women after radical surgical EC treatment. In addition to the previously verified improvement in the quality of life based on subjective questionnaires and scales, the effectiveness of the proposed medical rehabilitation program for such patients was confirmed by objective methods. This rehabilitation program can be recommended to all EC females in the recovery period after surgical treatment.